Correlação entre as características físicas e locacionais de lotes e o consumo efetivo médio per capta de água potável: estudo de caso da cidade de Bebedouro (SP) - Gaspar, Flávia Cristina (Universidade Federal de São Carlos, 2019)
Information pertaining to water consumption per capita can be considered as a valuable tool for the design of parts of the water supply system of a municipality. The difficulty to the urban infrastructure designer is the estimation of the average per capita water consumption to be adopted in a water supply system project. The general objective of this work was to evaluate the physical and locational characteristics of urban lots and to correlate them with the effective per capita consumption of water for the city of Bebedouro (SP). We analyzed 37 neighborhoods, all with 100% hydrometric and occupancy rate equal to or greater than 85%. From the analyzed data, it was verified that the average effective consumption per capita maintained a positive correlation with the average individual income, not being, however, observed a relation of the consumption with the gross population density related to the occupied area. It was observed that the water loss in distribution was 57.25% in the year 2015. Hypothesis test indicated that the independent variables Average Lot Area (AML), Standard Unit Value and Maximum Standard Unit Value (VUP / VUPmax) and of the number of inhabitants per link of water / lot (NHL) presented a linear correlation with the average daily effective consumption (qe), for interval and 95% confidence. The equation was determined from regression of multiple variables with determination coefficient R2 = 0.8099.
Correlation between lot physical and local characteristics and average effective percentage of drinking water: case study of the city of Bebedouro (SP)
Keywords: Sistema de abastecimento de água; Consumo efetivo per capita; Previsão de demanda; Water supply system; Effective per capita consumption; Forecast of demand; ENGENHARIAS